Influence of a complex impeller with tip clearance on the internal and external characteristics of a multiphase pump - Yao, Xin; Shi, Guangtai; Wen, Haigang; Huang, Zongliu (Frontiers in Energy Research, 2022)
With the exploitation of deep sea and desert oil fields, multiphase pumps have come into the public eye. However, due to the nature of the medium and operating environment, the performance of traditional multiphase pumps has diminished, leading to problems such as increased recovery cycles and rising costs. In order to obtain a high-head, high-reliability multiphase pump, this paper uses the model optimization method to design a complex pattern impeller. The best complex impeller with 17.25% increase in head was selected with the external characteristics as the optimization index, and a comparative analysis of the internal flow field was carried out between the complex impeller and original impeller when the inlet gas volume fraction was 10%. The results show that in the complex impeller, the short blade reduced the proportion of the high-speed zone, inhibited the appearance of the main blade suction surface low-speed zone, and significantly improved the return flow. The slope of the pressure boosting curve at the relative position 1.5–2.0 was increased, and the pressure boosting capacity was increased by 16.34 kPa. The short blade weakens the leakage movement while reducing the pressure effect on the main blade. In addition, the short blade not only improved the gas phase gathering but also reduced its size and made it closer to the main blade suction surface, which improved the uniformity of the gas phase distribution in the flow channel and also enhanced the inlet flow capacity. The results can provide a reference for future optimization and performance improvement of multiphase pump models.